Updraft Gasifier-Stirling Engine Biomass Incineration System Power Generation - Sookramoon, Krissadang (Trends in Sciences, 2022)
Biomass, the world’s largest renewable energy source, will continue to grow in the following energy markets. As a result, small biomass conversion systems are more competitive than large stand-alone converters because most of the biomass sources have low energy density and are widely distributed in space. The current study offers a small solid biomass power generation system to examine the possibility of direct connection of updates fixed bed gasifiers and a Stirling engine. The fixed bed updraft gasifier uses a combustion burner built into the gasifier to completely burn the synthetic gas produced by the gasifier. The exhaust gases generated by the synthesis gas combustion in the combustion tube are directed to the Stirling engine heater head. The engine then converts the heat contained in the exhaust gases. Output depends on the heat input. And the heat input is proportional to the flue gas flow rate and temperature Preliminary studies on the proposed straight couplings of the energy derived from the gasifier to mechanical energy of 300 mW and electrical energy of 50 mW. The outcomes of the Stirling engine with Updraft gasifier test shows that Pradauk biomass is more effective than charcoal biomass. Current research shows that no supplemental fuel is needed to keep the current system running smoothly. The technology and units presented can be considered as a viable solid biomass power generation system and enlarge to produce more electricity in rural areas of Thailand in the next step. HIGHLIGHTS The outcomes of the Stirling engine with Updraft gasifier test shows that Pradauk biomass is more effective than charcoal biomass The technology and units presented can be considered as a viable solid biomass power generation system and enlarge to produce more electricity in rural areas of Thailand in the next step Current studies show that the proposed system is technically feasible because it can generate electricity without interference so as to maintain an almost stable process GRAPHICAL ABSTRACT